Strategi Branding Produk UMKM Melalui Optimalisasi Digital Marketing dan Media Sosial di Era Transformasi Digital - Muhammad Robbiansa Pramadhika; Salsa Iswatun Nisa; Melia Kusnadi; Novita Putri; Sinar Mauliza Purnama; Muhamad Kosim (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The development of digital technology has significantly changed the global marketing landscape, providing a huge opportunity for Micro, Small, and Medium Enterprises (MSMEs) to build and strengthen their brands in a more effective, efficient, and affordable way. This research aims to examine and analyze digital branding strategies implemented by MSMEs in facing various challenges and taking advantage of opportunities that arise in the era of digital transformation. A qualitative descriptive approach was used in this study, with data collection through in-depth interviews, direct observations, and documentation studies on a number of MSME actors who actively utilize digital platforms. Interactive analysis techniques are used to process and analyze the data obtained systematically. The results of the study show that the strategic use of digital platforms such as social media, marketplaces, and websites has great potential in improving brand image, expanding market reach, and strengthening the competitiveness of MSME products in the midst of increasingly fierce competition. One of the key elements of successful digital branding is consistency in visual communication, relevant message delivery, and activeness in building interactions with customers. In addition, the use of digital marketing features such as paid advertising, creative content, influencer marketing, and customer relationship management also supports strengthening brand identity and consumer loyalty. However, the effectiveness of this strategy is greatly influenced by the level of digital literacy, access to technology, and managerial capacity of MSME actors. Therefore, support from the government and related institutions in the form of training, mentoring, and affirmative policies is needed to encourage inclusive and sustainable digital transformation. This research provides practical and theoretical